2000
DOI: 10.2134/agronj2000.92110x
|View full text |Cite
|
Sign up to set email alerts
|

Sugarbeet Nitrogen Uptake and Performance Following Heavily Fertilized Onion

Abstract: Crop over‐fertilization has economic and environmental consequences. Sugarbeet (Beta vulgaris L.) N fertilizer requirements could be lower than expected when planted after shallow rooted onion (Allium cepa L.). Sugarbeet was planted on an Owyhee silt loam (coarse‐silty, mixed, mesic Xerollic Durorthid) for 2 yr, where the previous onion crop had received 0, 60, 120, 240, and 480 kg N ha−1. Soil nitrate and ammonium were measured in 0.3‐m increments to 1.8 m deep after harvesting onion, and before and after gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
1
18
0
1
Order By: Relevance
“…This would be in line with the results of Shock et al [62], who found a negative relationship between nitrate concentration in petioles and polarization (albeit only for one of the two years of their study); with Pocock et al [63], who reported that late additions or releases of nitrogen from soil organic matter reduced the sucrose content; and with Draycott and Christenson [64] and Malnou, Jaggard and Sparkes [40], who indicated that an amount of nitrogen above the optimum had a negative effect on sugar yield. Gordo-Ingelmo [17] explained that beet reacts to nitrogen fertilization increases with a greater development of the leaves and roots, which can cause excessive consumption of sucrose and an increase of non-sugars.…”
Section: Nitrogen Content In Leaves Total Nitrogen Absorption and Casupporting
confidence: 93%
“…This would be in line with the results of Shock et al [62], who found a negative relationship between nitrate concentration in petioles and polarization (albeit only for one of the two years of their study); with Pocock et al [63], who reported that late additions or releases of nitrogen from soil organic matter reduced the sucrose content; and with Draycott and Christenson [64] and Malnou, Jaggard and Sparkes [40], who indicated that an amount of nitrogen above the optimum had a negative effect on sugar yield. Gordo-Ingelmo [17] explained that beet reacts to nitrogen fertilization increases with a greater development of the leaves and roots, which can cause excessive consumption of sucrose and an increase of non-sugars.…”
Section: Nitrogen Content In Leaves Total Nitrogen Absorption and Casupporting
confidence: 93%
“…Proper N management for sugar beet fertilisation can be useful, since a plentiful mineral N application increases the potential of nitrate leaching into groundwater and it also results in a high top growth of plants, a lower sucrose concentration and a higher level of impurities in the roots (Winter, 1990;Shock et al, 2000), thus decreasing the crop profitability. Carter and Traveller (1981) reported that sugar beet root quality has steadily decreased since the early 1950s with the increased use of N fertiliser.…”
Section: Introductionmentioning
confidence: 99%
“…In some cropping systems, fertilization also occurs in the fall of the year following harvest. However, over-fertilization is also common, in which little to no economic benefit results [9,10].…”
Section: Introductionmentioning
confidence: 99%